»Sintegre holokausto« – genocid gorenjskih Sintov - Toš, Marjan (Časopis za zgodovino in narodopisje, 2024)
Before the outbreak of the Second World War, there were 1,107 Roma individuals residing in the Drava region, which was part of Yugoslav Slovenia, alongside approximately 150 Sinti, who were indigenous to Gorenjska. Additionally, there were around 300 itinerant Sinti who were split between Austria and Slovenia. Following the occupation and dismemberment of Slovenia in April 1941, the Sinti in Gorenjska, located within the German occupation zone, were among the first groups to be subjected to mass imprisonment in Nazi facilities in Begunje. Subsequently, they were deported to Serbia, where numerous men managed to escape and join the partisans. However, most were confined in concentration camps in Serbia, predominantly at Staro Sajmište in Belgrade. There, they faced a fate similar to that of the Roma and Jewish populations, who were also subjected to mass arrests and systematic extermination during the initial stages of the occupation. While the Nazis sought to distinguish between Sinti and other Roma, both communities fell victim to the oppressive racial policies implemented during that era, including Slovene Roma and Sinti individuals.
Keywords: genocid; genocide; holocaust; holokavst; nacizem; nazism; Roma; Romi; Sinti; victims; žrtve